Surgical Management of Renal Cell Carcinoma Extending Into Venous System: A 20-Year Experience. (June 2018) - Xiao, X.; Zhang, L.; Chen, X.; Cui, L.; Zhu, H.; Pang, D.; Yang, Y.; Wang, Q.; Wang, M.; Gao, C.
Background and Aims: The purpose of this study is to report our 20-year experience with the surgical management of renal cell carcinoma extending into the inferior vena cava using a novel classification system. Materials and Methods: We retrospectively reviewed the data of 103 patients (69 males, 34 females, mean age: 52.9 ± 12.6 years) with renal cell carcinoma involving the venous system treated between 1993 and 2014. The inferior vena cava tumor thrombus was classified into five levels: 0 (renal vein, n = 12), 1 (infrahepatic, n = 33), 2a (low retrohepatic, n = 26), 2b (high retrohepatic, n = 19), and 3 (supradiaphragmatic, n = 13). Clinical data were summarized, and overall survival, cancer-specific survival, and disease-free survival were examined by Cox regression analysis. Results: All patients underwent radical surgery. Complete resections of the renal tumor and thrombus were achieved in 101 patients (98.1%). Two intraoperative and one postoperative in-hospital deaths (2.9%) occurred. In total, 19 patients (18.8%) had a total of 29 postoperative complications. Mean follow-up time was 46 months (range, 1–239 months). The 5- and 10-year overall survival rates were 62.9% and 56.0%, respectively. Metastasis, rather than thrombus level, was a significant risk factor associated with overall survival (hazard ratio = 4.89, 95% confidence interval: 2.24–10.67, p < 0.001). Conclusion: Our novel classification system can be used to select the optimal surgical approach and method for patients with renal cell carcinoma and venous thrombus. Its use is associated with prolonged survival and relatively few complications. Metastasis is an independent risk factor of overall survival.